A new species from the Clubiona caerulescens group from the Caucasus (Araneae: Clubionidae). Issue 4 (2nd October 2017) - Mikhailov, Kirill G.; Otto, Stefan; Japoshvili, George
Abstract : An illustrated description of Clubiona caucasica sp. n., which is closely related to C . caerulescens L. Koch, 1867 is provided. The new species is found in the Caucasus (Russia, Georgia, Azerbaijan, Armenia) and in Turkey (one locality). http://www.zoobank.org/urn:lsid:zoobank.org:pub:4C8851E2-CBBC-42E6-8600-585E757C9043